Relationship between Hepatitis B virus infection and platelet production and dysfunction. (17th February 2022) - Jiang, Huinan; Li, Yanwei; Sheng, Qiuju; Dou, Xiaoguang
Abstract: Hepatitis B virus (HBV) is a kind of hepatotropic DNA virus. The main target organ is liver, except for liver, HBV has been found in a variety of extrahepatic tissues, such as kidney, thyroid, pancreas, bone marrow, etc. HBV can cause severe complications by invading these tissues. Among them, pancytopenia is one of the common complications, especially thrombocytopenia that causes life-threatening bleeding. However, the mechanism of thrombocytopenia is unclear and the treatment is extremely difficult. It has been confirmed that HBV has a close relationship with platelets. HBV can directly infect bone marrow, inhibit platelet production, and accelerate platelet destruction by activating monocyte-macrophage system and immune system. While platelets act as a double-edged sword to HBV. On one hand, the activated platelets can degranulate and release inflammatory mediators to help clear the viruses. Furthermore, platelets can provide anti-fibrotic molecules to improve liver functions and reduce hepatic fibrosis. On the other hand, platelets can also cause negative effects. The infected platelets collect HBV-specific CD8 + T cells and nonspecific inflammatory cells into liver parenchyma, inducing chronic inflammation, liver fibrosis and hepatic carcinoma. This article explores the interaction between HBV infection and platelets, providing a theoretical basis for clinical treatment of thrombocytopenia and severe hemorrhage caused by HBV infection.